Acknowledging Cocaine Capital in Central American Development. Issue 2 (2nd December 2022) - Pearson, Zoe; Skiba, Alexandre; McSweeney, Kendra; Nielsen, Erik; Piccorelli, Justin
Cocaine trafficking has a significant but understudied influence on Central American economies. The economic implications of this trade have repercussions for both regional development and drug control policy debates, and therefore deserve greater attention. Towards that end, in this paper we provide estimates of 1) the value of trade of primary cocaine movements that were delivered to Central America, by country (excluding El Salvador) between 2000 and 2018; and 2) the value added by the cocaine trade to Central American economies. Due to limits in data availability, we compare several estimation approaches to impute missing price and volume data using information available to us. We then use available and imputed figures to estimate the value of cocaine movements for each country over time, and the value added as a measure of difference between the Central American country of arrival and the source country of Colombia. In interpreting and discussing our findings we draw attention to the economic pressures, volatility, and development challenges faced by countries that have become important waypoints in the cocaine trade because of supply-side cocaine control efforts.